Reconstruction of legal liability of philanthropic organisations in the misuse of humanitarian donations - Bango, Fikran S; Naswar, Naswar; Sapiddin, Andi Syahwiah A; Maskun, Maskun; Normiati, N; Kasim, Nur Mohamad; Syamsuddin, M. Yusuf (Jurnal Hukum Novelty, 2024)
Introduction to The Problem: The revelation of cases of misuse of humanitarian donations by philanthropic organizations reported by the media. The Aksi Cepat Tanggap (ACT) organization, which is one of the suspects in the misuse of humanitarian donations, is a big question about the implementation of supervision carried out by the government. There are not many cases of ACT, there are several institutions or community organizations to government organizations that have misused their donations. The form of misuse of humanitarian donations with the misuse of public funds to the waste of funds.Purpose/Objective Study: This research aims to reconstruct the legal liability of social philanthropy institutions in the misuse of humanitarian funds. Thus, the collection of humanitarian donations can provide real benefits to the community, and government programs related to poverty alleviation can have a real impact.Design/Methodology/Approach: This type of research is normative juridical with an analytical descriptive approach that discusses legal symptoms and problems with a legislative and doctrinal approach.Findings: The author identifies a significant gap in governmental oversight concerning the collection of money or goods intended for humanitarian aid. This lack of supervision has resulted in the opportunistic exploitation of disaster events, where individuals or groups capitalize on the urgency and generosity elicited by such crises. These actors collect donations ostensibly for relief efforts but instead divert these resources to serve their own personal or financial interests. The absence of stringent regulatory frameworks and effective monitoring mechanisms allows for this misuse, undermining public trust and depriving genuine victims of the essential aid they desperately need. The author underscores the critical need for robust government intervention and accountability measures to safeguard the integrity of humanitarian donations and ensure they reach those most in need.Keywords: Reconstruction; Philanthropic Institutions; Humanitarian Donations